External work is deficient in both limbs of patients with unilateral PAD - Wurdeman, Shane R. (2012)
External work was utilized to measure differences between the unaffected and the affected limb in patients with unilateral peripheral arterial disease compared to healthy controls. Patients with unilateral peripheral arterial disease have shown deficits in peak joint powers during walking in the unaffected and affected legs. However, no research has detailed the amount of work that is being performed by each leg compared to healthy controls even though such an analysis would provide valuable information on the energy output from the affected and the unaffected legs. Two hypotheses were tested: a) the unaffected and affected leg would perform less work than healthy controls in a pain-free state, and b) the onset of symptomatic claudication pain would result in further changes in the external work. Results showed that during a pain-free state, both the unaffected and affected legs perform less work than the healthy controls. After onset of claudication pain, the work output by the affected limb becomes further decreased while the unaffected limb experiences changes in negative external work. These findings combined with recent evidence of decreased peak powers in both legs in unilateral peripheral arterial disease patients reflects altered pathomechanics in both limbs compared to healthy controls.